Stability Analysis of Controlled DC Motor (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Controlled dc motors are nonlinear systems, thatshow a nonlinear action in their operation including, sub-harmonics and chaos when they work outside their designspecifications. This nonlinearity forces the motor changingits normal operation to a random-like behaviour; In thispaper, the nonlinear dynamics of DC motors areinvestigated. It is shown that the concept of the Poincarémap approach and the monodromy matrix method can besuccessfully applied to determine the stability of DC motors